2018
DOI: 10.1007/s10552-018-1013-4
|View full text |Cite
|
Sign up to set email alerts
|

A risk prediction model to allow personalized screening for cervical cancer

Abstract: A multivariable model using data from the electronic health record was able to stratify women across a 50-fold gradient of risk for CIN2+. After further validation, use of a similar model could enable more targeted cervical cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Several studies used logistic regression to establish predictors for histologic grade or risk stratification based on the epidemiologic risk factors and the molecular markers. In a large study of around 100,000 women using race, smoking status, insurance, marital status, median income, and previous HPV test result as predictors, their model only obtained an AUC of 0.81 for CIN2+ [ 19 ]. Another study of 1,477 women reported that the most predictive factors were mRNA level, DNA index, parity, and age, and the AUC was 0.99 for HSIL and 0.81 for LSIL [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies used logistic regression to establish predictors for histologic grade or risk stratification based on the epidemiologic risk factors and the molecular markers. In a large study of around 100,000 women using race, smoking status, insurance, marital status, median income, and previous HPV test result as predictors, their model only obtained an AUC of 0.81 for CIN2+ [ 19 ]. Another study of 1,477 women reported that the most predictive factors were mRNA level, DNA index, parity, and age, and the AUC was 0.99 for HSIL and 0.81 for LSIL [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is a potential advantage over other predictive models for CC, which typically rely on a specific set of patient data and risk factors. 16 , 17 Finally, our model assesses CC risk based on a limited list of risk factors rather than the risk of cervical pre-cancer based on CC screening results, such as the analysis reported by Rothberg et al 18 …”
Section: Discussionmentioning
confidence: 99%
“…This is a potential advantage over other predictive models for CC, which typically rely on a specific set of patient data and risk factors. 16,17 Finally, our model assesses CC risk based on a limited list of risk factors rather than the risk of cervical pre-cancer based on CC screening results, such as the analysis reported by Rothberg et al 18 The meta-model was also able to combine both adjusted and non-adjusted risk factor estimates. However, the use of both univariate and multivariate risk factor estimates could potentially bias predicted risks.…”
Section: Discussionmentioning
confidence: 99%
“…Additional risk factors for CC have been identified, but are not currently included in recommendations about screening intervals. These include age, smoking, oral contraceptive use, and sexual history [26]. Evaluating screening strategies that consider these risk factors for a more personalized approach, incl.…”
Section: An Alternative Policy Optionmentioning
confidence: 99%